2016
DOI: 10.3389/fmicb.2016.01145
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity and Community Structure of Supragingival Plaques in Adults with Dental Health or Caries Revealed by 16S Pyrosequencing

Abstract: Dental caries has a polymicrobial etiology within the complex oral microbial ecosystem. However, the overall diversity and structure of supragingival plaque microbiota in adult dental health and caries are not well understood. Here, 160 supragingival plaque samples from patients with dental health and different severities of dental caries were collected for bacterial genomic DNA extraction, pyrosequencing by amplification of the 16S rDNA V1–V3 hypervariable regions, and bioinformatic analysis. High-quality seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
121
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 93 publications
31
121
1
Order By: Relevance
“…Dental caries is major health problem in most countries. Similar to data of other studies, our survey demonstrated that patients with poorer oral hygiene have increased number of decayed, missing and filled teeth [6,7,17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dental caries is major health problem in most countries. Similar to data of other studies, our survey demonstrated that patients with poorer oral hygiene have increased number of decayed, missing and filled teeth [6,7,17].…”
Section: Discussionsupporting
confidence: 90%
“…According to survey in Ninth People's Hospital of Shanghai Jiao Tong University, treatment of dental caries should be aimed at balancing restoration and modulating interactions to oral microbiota [17]. Dental caries is major health problem in most countries.…”
Section: Discussionmentioning
confidence: 99%
“…They were also recovered from oral plaque of guinea pigs [21] and feces of piglets [54], dental plaque from healthy individuals, plaque and saliva from patients with various types of caries, gingivitis, chronic periodontitis, and peri-implantitis [23,2527,34,35,37,38,44,45,47,49,52,59,60,62,6669,91,94], decayed tooth surfaces and discordant caries from intact enamel surfaces [53]. Leptotrichia species were also isolated from bronchoalveolar lavage fluid, and patients with leukocytosis, hypoxemia, and dyspnea [24].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
“…Lactobacillus metabolizes dietary sugars immediately and produces acid which is cause decalcification of teeth. [2,17,29,30] In the deep dentinal lesions, acid producing Lactobacillus spp are found to be predominant. In the molecular perspective, both S. mutans and Lactobaccillus spp sometimes are at very low levels or even go undetected suggesting that initiation and progression of caries cannot be solely attributed to these traditionally causative bacteria.…”
Section: Discussionmentioning
confidence: 99%